TransLatin Joyce Global Transmissions in Ibero-American Literature - Price, B.; Salgado, C.; Schwartz, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
TransLatin Joyce explores the circulation of James Joyce's work in the Ibero-American literary system. The essays address Joycean literary engagements in Spain, Portugal, Argentina, Mexico, and Cuba, using concepts from postcolonial translation studies, antimodernism, game theory, sound studies, deconstruction, and post-Euclidean physics.
Keywords: America—Literatures.; British literature; Ethnology—Latin America; Literature—Philosophy.; European literature; Literature, Modern—20th century; North American Literature; British and Irish Literature; Latin American Culture; Literary Theory; European Literature; Twentieth-Century Literature